Evaluation of Nutritional Status and Yield Limiting Nutrients in Oil Palm Plantations of Cauvery Delta Zone of Tamil Nadu - K. Suresh; Ravi K. Mathur, Sanjib K. Behera, Arvind K. Shukla (Journal of the Indian Society of Soil Science, 2018)
Oil palm (Elaeis guineensis Jacq.) is grown in many countries, including India, to meet vegetable oil requirement. Assessment of soil properties and leaf nutrient concentration in oil palm plantations is required for effective nutrient management and higher crop yield. Therefore, the present study was carried out by analyzing 104 soil samples and 52 leaf samples collected from oil palm plantations of Thanjavur district of Tamil Nadu, India. The soil properties like pH, electrical conductivity (EC), organic carbon (OC), available nitrogen (N), phosphorus (P), potassium (K), exchangeable calcium (Ca) and magnesium (Mg) and available sulphur (S) and boron (B) in 0-20 and 20-40 cm soil depth varied widely with CV values ranging from 7.44 to 89.4%. Leaf nutrient concentration varied from 1.11 to 3.17, 0.05 to 0.18, 0.21 to 0.98, 1.24 to 2.23, 0.17 to 0.86, 0.08 to 0.22% and 21.8 to 77.7 mg kg-1 for N, P, K, Ca, Mg, S and B, respectively. Diagnosis and recommendation integrated system (DRIS) norms and indices were derived from different nutrient expressions. The order of requirement of leaf nutrients was found to be K > P > N > Mg > B. Optimum leaf nutrient range for N, P, K, Mg and B were estimated as 1.61 to 2.11%, 0.10 to 0.12%, 0.33 to 0.81%, 0.23 to 0.73% and 30.6 to 54.8 mg kg-1, respectively, which could be used for guiding balanced application of fertilizers. On the whole, 15, 31, 2, 8 and 10% of leaf samples had below optimum concentrations of N, P, K, Mg and B, respectively.